Human growth and development across the lifespan applications for counselors - Capuzzi, Dave; Stauffer, Mark D. (Wiley, 2016)
"Human Development Across the Life Span is a practical guide to human growth and development, moving beyond theory to include real-world applications for counselors who work with clients.This book is the only text on human growth and development that emphasizes the key implications and applications for counselors, providing useful information and the insights of real experts in each subject area"--Provided by publisher.